Mrs. Jafee is daffy! - Gutman, Dan; Paillot, Jim (New York, NY Scholastic Inc., 2016)
When the new vice principal is put in charge of Ella Mentry School for a few days, she tries out some very unusual ideas about how students learn.
110803
Keywords: Elementary schools -- Juvenile fiction; School principals -- Juvenile fiction; Schools; Humorous fiction; Juvenile works